A systematic typology and synthesis of aquatic refuges in freshwater ecosystems - Matthieu Lucchini; Loïc Trutin; Jean-Nicolas Beisel; Cybill Staentzel (Science of The Total Environment, 2026)

Interplay of Aquatic and Riparian Variables in Two Anthropogenically-Influenced Small Stream Catchments - Alexander Feckler; Sebastian Stehle; Jean-Nicolas Beisel; Etienne Chanez; Tanja J. Joschko; Alexis P. Roodt; Thomas Schmidt; Verena C. Schreiner; Ralf Schulz; Cybill Staentzel; Jens Schirmel (Archives of Environmental Contamination and Toxicology, 2026)

Proposal for a method to assess the habitat mosaic heterogeneity of a river bottom using fine-scale spatial analysis - Jean-Nicolas Beisel; Cybill Staentzel (Hydrobiologia, 2025)

Impact of non-native fish on macroinvertebrate communities of insular tropical small standing waters - Frédéric Labat; Jean-Nicolas Beisel (Hydrobiologia, 2025)

Quantitative Estimates of Nutrient Inputs From Angling Baits in Lakes Supporting Different Recreational Fisheries - Alexis Imbert; Stéphanie Boulêtreau; Jean‐Nicolas Beisel; Julien Cucherousset (Fisheries Management and Ecology, 2025)
Recreational anglers use ground baiting to attract fish and increase catch inputs organic matter that can have important effects on water quality by increasing eutrophication. However, nutrient inputs from angling bait by recreational fisheries have not yet been estimated. We quantified nutrient inputs from angling baits in small lakes supporting specialized carp, put‐and‐take, and specialized roach recreational fisheries with a 2‐year field survey of angling activity and in‐person angler questionnaires. Angling activity was highly variable among recreational fisheries and averaged 82 (±74 SD) angler‐day/ha/year in lakes with specialized carp fisheries, 145 (±80) in lakes with put‐and‐take fisheries, and 36 (±18) in lakes with specialized roach fisheries. Angling activity also differed temporally among recreational fisheries, with high angling activity in spring and summer for specialized carp and specialized roach fisheries, and in autumn and winter for put‐and‐take fisheries. The type and amount of baits used by anglers strongly differed among recreational fisheries, with specialized carp anglers using boilies (2.5 ± 1.5 SD kg/angler/day) and seeds (2.1 ± 1.9 kg/angler/day), put‐and‐take anglers using exclusively pellets (0.39 ± 0.15 kg/angler/day), and specialized roach anglers using ground baits (0.72 ± 0.36 kg/angler/day). Nutrient inputs from angling baits were highly variable among recreational fisheries and ranged from 0.5 (±0.2 SD) kg/ha/year of nitrogen and 0.1 (±0.0) kg/ha/year of phosphorus in specialized roach fisheries to 10.2 (±9.3) kg/ha/year of nitrogen and 1.6 (±1.5) kg/ha/year of phosphorus in specialized carp fisheries. Our findings revealed that ecological consequences of ground baiting differed among recreational fisheries, which should be useful for developing fishery‐specific regulations to efficiently manage ground baiting.

A comparative analysis of eDNA metabarcoding and field surveys: Exploring freshwater plant communities in rivers - Armando Espinosa Prieto; Laurent Hardion; Nicolas Debortoli; Thibaut Bournonville; Thibaut Mathot; Jonathan Marescaux; Etienne Chanez; Cybill Staentzel; Jean-Nicolas Beisel (Science of The Total Environment, 2024)

A global systematic map of knowledge of inland commercial navigation effects on freshwater ecosystems - Alienor Jeliazkov; Vanesa Martínez-Fernández; Vassil Y. Altanov; Jean-Nicolas Beisel; Anthonie Dirk Buijse; Sofia Consuegra; Swann Felin; Carlos Garcia de Leaniz; Wolfram Graf; Fengzhi He; Sonja C. Jähnig; Patrick Leitner; et al. (Journal of Environmental Management, 2024)

Morphological vs. DNA metabarcoding approaches for the evaluation of stream ecological status with benthic invertebrates: Testing different combinations of markers and strategies of data filtering - Albin Meyer; Frédéric Boyer; Alice Valentini; Aurélie Bonin; Gentile Francesco Ficetola; Jean‐Nicolas Beisel; Jonathan Bouquerel; Philippe Wagner; Coline Gaboriaud; Florian Leese; Tony Dejean; Pierre Taberlet; et al. (Molecular Ecology, 2021)
Macroinvertebrate assemblages are the most common bioindicators used for stream biomonitoring, yet the standard approach exhibits several time‐consuming steps, including the sorting and identification of organisms based on morphological criteria. In this study, we examined if DNA metabarcoding could be used as an efficient molecular‐based alternative to the morphology‐based monitoring of streams using macroinvertebrates. We compared results achieved with the standard morphological identification of organisms sampled in 18 sites located on 15 French wadeable streams to results obtained with the DNA metabarcoding identification of sorted bulk material of the same macroinvertebrate samples, using read numbers (expressed as relative frequencies) as a proxy for abundances. In particular, we evaluated how combining and filtering metabarcoding data obtained from three different markers (COI: BF1‐BR2, 18S: Euka02 and 16S: Inse01) could improve the efficiency of bioassessment. In total, 140 taxa were identified based on morphological criteria, and 127 were identified based on DNA metabarcoding using the three markers, with an overlap of 99 taxa. The threshold values used for sequence filtering based on the “best identity” criterion and the number of reads had an effect on the assessment efficiency of data obtained with each marker. Compared to single marker results, combining data from different markers allowed us to improve the match between biotic index values obtained with the bulk DNA versus morphology‐based approaches. Both approaches assigned the same ecological quality class to a majority (86%) of the site sampling events, highlighting both the efficiency of metabarcoding as a biomonitoring tool but also the need for further research to improve this efficiency.

Ecological implications of the replacement of native plant species in riparian systems: unexpected effects of Reynoutria japonica Houtt. leaf litter - Staentzel Cybill; Rouifed Soraya; Beisel Jean-Nicolas; Hardion Laurent; Poulin Nicolas; Combroux Isabelle (Biological Invasions, 2020)

Spatiotemporal trends for exotic species in French freshwater ecosystems: where are we now? - Beisel Jean-Nicolas; Peltre Marie-Christine; Kaldonski Nicolas; Hermann Agnès; Muller Serge (Hydrobiologia, 2017)

Assessing filtration rates of exotic bivalves: dependence on algae concentration and seasonal factors - Jonathan Marescaux; Elodie Falisse; Julien Lorquet; Karine Van Doninck; Jean-Nicolas Beisel; Jean-Pierre Descy (Hydrobiologia, 2016)

Benthic macro-invertebrate fauna associated with Dreissena mussels in the Meuse River: from incapacitating relationships to facilitation - Jonathan Marescaux; Adrien Latli; Julien Lorquet; Julie Virgo; Karine Van Doninck; Jean-Nicolas Beisel (Aquatic Ecology, 2016)

Increase in Developmental Instability in a Field-Collected Chironomus Population Maintained Under Laboratory Conditions - Hélène Arambourou; Philippe Branchu; Jean-Nicolas Beisel (Bulletin of Environmental Contamination and Toxicology, 2015)

Proposal for a simple hydromorphological habitat survey method for freshwater bivalve (Unionidae) inventories - Florent Lamand; Jean-Nicolas Beisel (Aquatic Ecology, 2014)

Field evidence for non-host predator avoidance in a manipulated amphipod - Vincent Médoc; Jean-Nicolas Beisel (The Science of Nature, 2009)

Geographic patterns in freshwater gammarid invasions: an analysis at the pan-European scale - Simon Devin; Jean-Nicolas Beisel (Aquatic Sciences, 2008)

An acanthocephalan parasite increases the salinity tolerance of the freshwater amphipod Gammarus roeseli (Crustacea: Gammaridae) - Christophe Piscart; Dennis Webb; Jean Nicolas Beisel (The Science of Nature, 2007)

Biological and ecological characteristics of invasive species: a gammarid study - Simon Devin; Jean-Nicolas Beisel (Biological Invasions, 2006)

Monitoring Changes in Freshwater Macroinvertebrate Communities Along a Salinity Gradient Using Artificial Substrates - Christophe Piscart; Jean-Claude Moreteau; Jean-Nicolas Beisel (Environmental Monitoring and Assessment, 2006)

Biodiversity and Structure of Macroinvertebrate Communities Along a Small Permanent Salinity Gradient (Meurthe River, France) - Christophe Piscart; Jean-Claude Moreteau; Jean-Nicolas Beisel (Hydrobiologia, 2005)

Patterns of Biological Invasions in French Freshwater Systems by Non-Indigenous Macroinvertebrates - Simon Devin; Loïc Bollache; Pierre-Yves Noël; Jean-Nicolas Beisel (Hydrobiologia, 2005)

Biodiversity patterns along a salinity gradient: the case of net-spinning caddisflies - Christophe Piscart; Antoine Lecerf; Philippe Usseglio-Polatera; Jean-Claude Moreteau; Jean-Nicolas Beisel (Biodiversity and Conservation, 2005)

Changes in functional biodiversity in an invaded freshwater ecosystem: the Moselle River - Simon Devin; Jean-Nicolas Beisel; Philippe Usseglio-Polatera; Jean-Claude Moreteau (Hydrobiologia, 2005)

The spatial heterogeneity of a river bottom: a key factor determining macroinvertebrate communities - Jean-Nicolas Beisel; Philippe Usseglio-Polatera; Jean-Claude Moreteau (Hydrobiologia, 2000)

Stream community structure in relation to spatial variation: the influence of mesohabitat characteristics - Jean-Nicolas Beisel; Philippe Usseglio-Polatera; Sandra Thomas; Jean-Claude Moreteau (Hydrobiologia, 1998)